Plasma immunoreactive endothelin levels in children with cystic fibrosis. - Siahanidou, T; Nicolaidou, P; Nikolaidou, P; Doudounakis, S; Georgouli, E; Papadimitriou, A; Karpathios, T. (Acta Paediatr, 2000)
UNLABELLED: Plasma immunoreactive endothelin levels were determined in 31 children and adolescents with cystic fibrosis and it was examined whether these levels correlated with the severity of the disease. The study comprised 16 cystic fibrosis patients (mean (SD) age 13.0 (4.9) y) with impaired lung function (Group A), 15 cystic fibrosis patients (11.2 (5.5) y) with unimpaired lung function (Group B) and 28 healthy controls (10.6 (4.3) y) (Group C). The selection and classification of patients into groups was based on criteria including the grade of finger-clubbing, the Brasfield chest radiograph score and spirometric and arterial blood gas values. In all subjects, plasma immunoreactive endothelin, atrial natriuretic peptide, renin, serum aldosterone levels and serum and urine electrolytes were measured. CONCLUSIONS: Plasma endothelin levels were significantly higher in Group A (range 2.5-8.4 pg/ml, median 3.2 pg/ml) than those in Group B (1.3-3.8 pg/ml, median 2.0 pg/ml, p < 0.001) and Group C (1.5-3.5 pg/ml, median 2.5 pg/ml, p < 0.001), whereas they did not differ between groups B and C. They correlated positively with the severity of finger-clubbing, heart rate, arterial blood PCO2, plasma atrial natriuretic peptide levels and serum aldosterone levels and negatively with the arterial blood PO2, forced vital capacity (FVC), forced expiratory volume in 1 sec (FEV1) and the Brasfield chest radiograph score. In multivariate regression analysis PO2 was the only independent factor found to significantly affect plasma endothelin levels. In conclusion, plasma immunoreactive endothelin levels are increased in cystic fibrosis patients with impaired pulmonary function and are related to the severity of the disease.
Keywords: Adolescent; Atrial Natriuretic Factor; Child; Cystic Fibrosis; Endothelins; Female; Humans; Male; Prospective Studies; Respiratory Function Tests; Severity of Illness Index